Signaling Cascades Governing Cdc42-Mediated Chondrogenic Differentiation and Mensenchymal Condensation. Issue 3 (6th January 2016) - Wang, Jirong; Wang, Chaojun; Xu, Chengyun; Wu, Xiaokai; Hong, Dun; Shi, Wei; Gong, Ying; Chen, Haixiao; Long, Fanxin; Wu, Ximei
Abstract: Endochondral ossification consists of successive steps of chondrocyte differentiation, including mesenchymal condensation, differentiation of chondrocytes, and hypertrophy followed by mineralization and ossification. Loss-of-function studies have revealed that abnormal growth plate cartilage of the Cdc42 mutant contributes to the defects in endochondral bone formation. Here, we have investigated the roles of Cdc42 in osteogenesis and signaling cascades governing Cdc42-mediated chondrogenic differentiation. Though deletion of Cdc42 in limb mesenchymal progenitors led to severe defects in endochondral ossification, either ablation of Cdc42 in limb preosteoblasts or knockdown of Cdc42 in vitro had no obvious effects on bone formation and osteoblast differentiation. However, in Cdc42 mutant limb buds, loss of Cdc42 in mesenchymal progenitors led to marked inactivation of p38 and Smad1/5, and in micromass cultures, Cdc42 lay on the upstream of p38 to activate Smad1/5 in bone morphogenetic protein-2-induced mesenchymal condensation. Finally, Cdc42 also lay on the upstream of protein kinase B to transactivate Sox9 and subsequently induced the expression of chondrocyte differential marker in transforming growth factor-β1-induced chondrogenesis. Taken together, by using biochemical and genetic approaches, we have demonstrated that Cdc42 is involved not in osteogenesis but in chondrogenesis in which the BMP2/Cdc42/Pak/p38/Smad signaling module promotes mesenchymal condensation and the TGF-β/Cdc42/Pak/Akt/Sox9 signaling module facilitates chondrogenic differentiation.